Characterization of the edaphic mesofauna in five grassland agroecosystems of Granma province, Cuba - Chávez Suárez, Licet; Estrada Prado, W.; Labrada Hernández, Yaquelín; Rodríguez García, Idalmis; Herrera Villafranca, Magalys (Cuban Journal of Agricultural Science, 2019)
The edaphic mesofauna performs essential functions in the soil such as the recycling of nutrients and formation of its microstructure. The objective of this research was to characterize the edaphic mesofauna in five grassland agroecosystems of Granma province, Cuba. To this end, contrasting agroecosystems were selected in terms of soil type, grassland and productive purpose (“Estación de Pastos”, “Ojo de agua”, "El Triángulo", "El Progreso" and "Cupeycito"). The pitfall traps were used, with a 0.003 % detergent solution. The individuals were extracted and counted and placed in vials, with 70 % ethanol, for later identification. Individuals belonging to two classes, four orders, six families and seven genera were found. The Collembola order was the best represented with five genera. Only in the third sampling there was a significant influence of the season detected on some of the studied variables, specifically for each agroecosystem. The Shannon index showed values lower than 1.35; while the dominance indexes showed values close to or higher than 0.5 in most cases. It is concluded that the richness and abundance of the edaphic mesofauna in the studied grassland agroecosystems was low and very variable in both climatic periods. Individuals belonging to the trophic categories of predators and detritivores were found which showed a variable relative abundance, in each agroecosystem and sampling performed; except in the “Estación de Pastos” where there was a predominance of predators. Key words: acari, collembolans, grasses, soils, pitfall traps